Establishment and evaluation of a UPLC-MS/MS method for simultaneous determination of bongkrekic acid and dehydroacetic acid in rice noodles - Zhao, Lingguo; Lv, Ronggui; Song, Jiang; Chen, Xi; Lei, Lei; Zeng, Weixian; She, Miaowen; Li, Dabing; Yu, Xiaxia; Liu, Zhanguo; Wang, Xiao; Liu, Yong (Frontiers in Chemistry, 2025)
A UPLC-MS/MS method with one-step extraction and simultaneous determination of bongkrekic acid (BA) and dehydroacetic acid (DHA) in rice noodles has been established in this study for the first time. The extraction solvent consisted of a mixture of methanol, ammonia, and water. Electrospray ionization negative ion mode (ESI-) was used for multiple reaction detection and external standard method was used for quantitative determination. The method demonstrated a good linearity range of 0 to 50 ng/mL with a correlation coefficient (r) of 0.9998 for BA, and showed a linearity range of 0 500 ng/mL with r of 0.9993 for DHA. The limits of detection (LOD) were determined to be 0.1 μg/kg for BA and 0.6 μg/kg for DHA. Additionally, the method exhibited good recovery of 90.1% 105.4% for BA and 80.4% 102% for DHA.